Evaluation of Salivary Gland Lesions by Fine Needle Aspiration Cytology at a Tertiary Care Hospital, Western Nepal - Poudel A; Shrestha B; Regmi S (Dove Medical Press, 2020)
Anuj Poudel,1 Bigya Shrestha,2 Sudeep Regmi3 1Department of Pathology, Universal College of Medical Sciences, Bhairahawa, Nepal; 2Department of Pathology, Hospital for Advanced Medicine & Surgery (HAMS), Kathmandu, Nepal; 3Department of Pathology, Manipal College of Medical Sciences, Pokhara, NepalCorrespondence: Anuj PoudelUniversal College of Medical Sciences, Bhairahawa, NepalEmail dranujpoudel@gmail.comBackground: Salivary gland tumors (SGTs) account for 2– 6.5% of all head and neck neoplasms, and fine needle aspiration cytology (FNAC) is one of the most useful diagnostic methods for clinicians. FNAC is utilized for evaluating suspicious salivary gland lesions initially. This study was undertaken to evaluate the various cytomorphological features of non-neoplastic and neoplastic lesions of salivary gland as diagnosed by FNAC.Materials and Methods: This prospective, analytical study was done for a period of 18 months from January 1, 2014 to June 31, 2016 at the Universal College of the Medical Sciences Teaching Hospital (UCMS-TH), Bhairahawa, Nepal. A total of 81 FNAC samples were collected from patients with salivary gland swelling. The lesions were evaluated cytologically and correlations with histopathological follow-up data were acquired in 31 cases. All statistical analyses were performed utilizing Statistical Package for Social Sciences (SPSS) software (version 24). Sensitivity and specificity of FNAC were evaluated and compared to that of biopsy.Results: Out of the 81 cases studied, females of 21– 30 years of age were the most commonly affected. The most common site of involvement was the parotid gland, with a frequency of 66.7%, the predominant benign lesion diagnosed cytologically was pleomorphic adenoma (PA), with a frequency of 51.84%, and the most common malignant lesion diagnosed was mucoepidermoid carcinoma (MEC), with a frequency of 9.88%. Of the total (N=81), 19.75% were of pediatric and 80.25% were in the adult age group. Within the pediatric age group, all the lesions diagnosed by FNAC were benign, with the most common lesion being PA. In the total cases evaluated for FNAC, biopsy sample was collected from 31 cases for histological correlation, with 90.32% corroborating the FNAC diagnosis.Conclusion: The study demonstrated that FNAC is a very useful, rapid, and minimally invasive diagnostic tool for salivary gland lesions that can be utilized for subsequent therapeutic case management.Keywords: fine needle aspiration cytology, FNAC, salivary gland lesions, Nepal